Identification of Probiotic Potential Lactobacillus from Mandai using Biochemical Test - Hussain, Nur Zaidatul Ilya; Sabran, Siti Fatimah (Enhanced Knowledge in Sciences and Technology, 2025)
In this research, only Lactobacillus species originating from mandai were evaluated for their probiotic characteristics to determine their usability as functional ingredients in chempedak inner skin fermentation. Mandai, a traditional fermented food from chempedak (Artocarpus integer), holds potential as probiotic source yet limited research exists on its beneficial microbes, particularly Lactobacillus species. This study analysed mandai fermentation over 28 days revealing a peak lactic acid bacteria (LAB) count 2.75 x 10⁴ CFU/g on day 7, followed by a decline to 1.40 x 10⁴ CFU/g, indicating optimal conditions for probiotic viability early in fermentation. Gram-staining confirmed the presence of Gram-positive, rod-shaped Lactobacillus. These findings suggest mandai’s potential as a natural probiotic, supporting the functional food development with further research needed for molecular characterization and in vivo validation.